Does higher fiscal deficit lead to rise in interest rates?: an empirical investigation - Goyal, Rajan (2004)
The relationship between fiscal deficit and the rate of interest is still an unsettled issue. Theoretically, at least in neo-classical sense, funding of government requirements through market borrowings would not only induce rise in interest rates, but the increased funding cost in turn would also contribute to the rise in fiscal deficit. In the Indian context, the coexistence of falling interest rates and growing size of fiscal deficit in the recent years, however, seems to suggest that the causation between the two does no hold. Further, there is empirical evidence suggesting one-way causality running only from real interest rate to fiscal deficit. This paper re-examines this issue and argues that the absence of an apparent fiscal impact on interest rate is essentially the result of higher liquidity in the system. Empirical results drawn through a VAR model show that there is a two-way causality between gross fiscal deficit and the real interest rate. -Reproduced.
Keywords: Interest rates